Association between passive smoking and Mycobacterium tuberculosis infection in children with household TB contact - Novaily Zuliartha; Ridwan M. Daulay; Melda Deliana; Wisman Dalimunthe; Rini Savitri Daulay (Indonesian Pediatric Society, 2015)
Background Tuberculosis (TB) and cigarette consumption are relatively high in Indonesia. Passive smoking may increase the risk of infection and disease in adults and children exposed to TB. An association between passive smoking and Mycobacterium tuberculosis infection in children has not been well documented. Objective To assess for an association between passive smoking and M. tuberculosis infection in children who had household contact with a TB patient. Methods This cross-sectional study was conducted in February and March 2011. Children aged 5 to 18 years who had household contact with a TB patient underwent tuberculin testing for M. tuberculosis infection. Subjects were divided into two groups: those exposed to passive smoke and those not exposed to passive smoke. Chi-square test was used to assess for an association between passive smoking and M. tuberculosis infection. Results There were 140 children enrolled in this study, with 70 exposed to passive smoke and 70 not exposed to passive smoke. Prevalence of M. tuberculosis infection was significantly higher in the passive smoking group than in those not exposed to passive smoke [81.4% and 52.9%, respectively, (P= 0.0001)]. In the passive smoking group there were significant associations between nutritional state, paternal and maternal education, and M. tuberculosis infection. But no associations were found between M. tuberculosis infection and familial income or BCG vaccination. Conclusion Among children who had household contact with a TB patient, they who exposed to passive smoke are more likely to have M. tuberculosis infection compared to they who not exposed to passive smoke.